Lamin A N-terminal phosphorylation is associated with myoblast activation: impairment in Emery–Dreifuss muscular dystrophy. Issue 3 (2nd March 2005) - Cenni, V; Sabatelli, P; Mattioli, E; Marmiroli, S; Capanni, C; Ognibene, A; Squarzoni, S; Maraldi, N M; Bonne, G; Columbaro, M; Merlini, L; Lattanzi, G
Abstract : Background: Skeletal muscle disorders associated with mutations of lamin A/C gene include autosomal Emery–Dreifuss muscular dystrophy and limb girdle muscular dystrophy 1B. The pathogenic mechanism underlying these diseases is unknown. Recent data suggest an impairment of signalling mechanisms as a possible cause of muscle malfunction. A molecular complex in muscle cells formed by lamin A/C, emerin, and nuclear actin has been identified. The stability of this protein complex appears to be related to phosphorylation mechanisms. Objective: To analyse lamin A/C phosphorylation in control and laminopathic muscle cells. Methods: Lamin A/C N-terminal phosphorylation was determined in cultured mouse myoblasts using a specific antibody. Insulin treatment of serum starved myoblast cultures was carried out to evaluate involvement of insulin signalling in the phosphorylation pathway. Screening of four Emery–Dreifuss and one limb girdle muscular dystrophy 1B cases was undertaken to investigate lamin A/C phosphorylation in both cultured myoblasts and mature muscle fibres. Results: Phosphorylation of lamin A was observed during myoblast differentiation or proliferation, along with reduced lamin A/C phosphorylation in quiescent myoblasts. Lamin A N-terminus phosphorylation was induced by an insulin stimulus, which conversely did not affect lamin C phosphorylation. Lamin A/C was also hyperphosphorylated in mature muscle, mostly in regenerating fibres. Lamin A/C phosphorylation was strikingly reduced in laminopathic myoblasts and muscle fibres, while it was preserved in interstitial fibroblasts. Conclusions: Altered lamin A/C interplay with a muscle specific phosphorylation partner might be involved in the pathogenic mechanism of Emery–Dreifuss muscular dystrophy and limb girdle muscular dystrophy 1B.